Globalization and the island economies of the South Pacific - Rukmani Gounder; V. Xayavong (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper examines the impact of increasing integration of the island economies of the South Pacific into expanding international markets, particularly that of Fiji and the Solomon Islands. Since the 1980s, globalization of the world economy has altered dramatically the volume and character of international resource flow. This has provided small island economies financing for international transactions, competitiveness, and diffusion of international financial markets. Trade, capital mobility, foreign direct investment (FDI) and foreign aid flows have become an important feature for most of these economies. It is unclear whether the island economies in fact have benefited from the globalization of international markets. The paper empirically tests how capital flows (i.e. FDI, aid flows) savings, trade (exports, and imports) affect growth. Thus, evaluation of the macroeconomic impact for these economies suggests some policy implications for the island nations economic performance and growth. – globalization ; aid dependence ; growth ; South Pacific island economies.
Keywords: F35; O11; O40; O56; 330; Insel; Kleinstaat; Kapitalmobilität; Außenwirtschaft; Südpazifischer Inselraum; Fidschi; Salomonen